SMART SHOPPING IN CONSUMER BEHAVIOUR OF POLISH SENIORS (REPORT FROM OWN RESEARCH) - Zalega, Tomasz (Acta Scientiarum Polonorum. Oeconomia, 2017)
The observed demographic changes involving mainly progressive ageing of the Polish population are leading to increased market importance of the senior consumer segment. More and more seniors are following new consumer trends, including smart shopping. The article aims to provide some insight into smart shopping, as well as to outline the factors influencing the dissemination of such shopping behaviours, with a broader reference to consumer behaviours of Polish seniors. The first part very synthetically explains the concept and key determinants of the smart shopping consumer trend. The next section focuses on the research conceptualisation and a description of the sample and its characteristics. Based on the conducted research, the last part sheds light on seniors’ consumer behaviour and attempts to define the extent to which seniors do smart shopping when making consumer decisions.